GLUCOSE LEVELS IN LATE PRETERM AND TERM NEWBORNS AT ONE HOUR OF LIFE AND FREQUENCY OF HYPOGLYCEMIA: Glucose Levels in Late Preterm and Term Newborns - Afzal, Muhammad; Yaqoob, Asma; Afzal, Alizay Gohar; khan, Kashmala; Wahab, Abdul (Pakistan Armed Forces Medical Journal, 2015)
Objective: To determine glucose levels in late preterm and term newborns at one hour of life in our population, along with the frequency of symptomatic hypoglycemia and it’s known risk factors.Study Design: Descriptive studyPlace and Duration of Study: Quaid-e-Azam International Hospital (QIH) Islamabad from July 2012 to September 2013.Material and Methods: Two hundred and seventy newborns were selected by consecutive purposive non probability sampling who were born at QIH either by spontaneous vaginal delivery or cesarean section. Only healthy neonates were included. Gestational age, weight, fetal and maternal risk factors were assessed. Glucose level was measured by glucometer at 1 hour of life after first feed. Neonates that became symptomatic with low glucose levels were thoroughly studied, readings reconfirmed from laboratory and were promptly managed.Results: Thirty (11%) babies showed sugar level < 30 mg/dl at 1 hour of life. Out of them 18(60%) were late preterm and 12(40%) were term babies. Out of them 12(40%) babies weighed